(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
This article talks about the main legislative changes occurred in relation to the humans traffi cking crime, in both its domestic and international modalities, including, its procedural aspects related to the prosecution of this crime, all focused on an investigative and practical perspective.